AN EVALUATION ON SHAREHOLDERS WEALTH CREATION BY BESCOM AT BENGALURU - Yogitha H; Dr. Leela M H (EPRA International Journal of Research and Development (IJRD), 2022)
Bangalore Electricity Supply Company Limited is responsible for Power distribution in eight districts of Karnataka state. The BESCOM ltd commence its business activity from 2002. The study tries to relate the financial concepts to the actual functioning of the company. The objective of the study is to analyse the financial performance of last five years. The study is based on secondary data and analysed using financial tools and techniques includes DuPont analysis and coefficient of correlation. The study brings out return on equity data to strengthen the shareholders wealth. The study also finds the relationship between the income and expenses.